Digital Employment Contract Practices (Contentpreuner – Mediapreuner) Media Industry in Indonesia - Faizin, Mu'adil (Jurnal Hukum dan Kenotariatan, 2023)
The practice of digital-based work contracts is experiencing rapid development, one form of business that uses digital-based work contracts, namely Mediapreuner, an example of a fairly large Mediapreuner business model in Indonesia, namely the Pikiran Rakyat Media Network (PRMN). The reality found on the ground, digital work contracts have been carried out massively, even by business networks that are national in scale. This seems to reconstruct the work contract culture that has been widely practiced by business people, starting from the MoU process. This then encourages researchers to carry out an in-depth observation process to dissect the engagement scheme, clauses in the contract, as well as the factors that influence business people to trust each other in digital work contracts. The practice of digital contracts of work at PRMN is an agreement in the form of cooperation between 3 parties. Strong reasons that encourage parties to be able to organize and maintain digital employment contracts are the parties' trust and track record of income.